2006
DOI: 10.1002/scj.20076
|View full text |Cite
|
Sign up to set email alerts
|

Japanese–English cross-language information retrieval integrating query and document translation methods

Abstract: SUMMARYIn cross-language information retrieval the search query and documents may undergo translation; here the question of how the task is converted into a monolingual information retrieval problem is of significant importance. The method that we propose in this research involves translating the query into the language of the document collection and performing a search on the basis of this; in addition, we apply machine translation to the returned documents converting them to the language of the user and refi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…In pivot method, before converting the words of a source language into the target language, source language words are firstly converted into pronunciation symbol and then converted into target language words. Pronunciation symbol is the International Phonetic Alphabet for notation of all languages [40,63] Translation helps individual to communicate in nonnative languages. But it is still very difficult to remove the language barrier.…”
Section: Back Translationmentioning
confidence: 99%
“…In pivot method, before converting the words of a source language into the target language, source language words are firstly converted into pronunciation symbol and then converted into target language words. Pronunciation symbol is the International Phonetic Alphabet for notation of all languages [40,63] Translation helps individual to communicate in nonnative languages. But it is still very difficult to remove the language barrier.…”
Section: Back Translationmentioning
confidence: 99%
“…In the second step, for any pair of European word e and Japanese Katakana word j, we examine whether or not j is a transliteration of e. For this purpose, we use a transliteration method [7]. If either e or j can be transliterated into its counterpart, we extract (e,j) as a transliteration-equivalent pair.…”
Section: Extracting Synonymsmentioning
confidence: 99%
“…If p(s|t) = 0, t is not a transliteration of s. p(t) denotes the probability that t is generated as a word in the target language [7]. However, in our case we always set p(t) = 1, because our purpose is to check whether or not two given words comprise a transliteration pair.…”
Section: Extracting Synonymsmentioning
confidence: 99%
“…It is similar to transliteration, but no phonetic elements are included. The technique bears some resemblance to query translation and transliteration research reported in Fujii and Ishikawa (2001). Fujii and Ishikawa use character-based rules to establish mapping between English characters and romanized Japanese katakana characters.…”
Section: Introductionmentioning
confidence: 99%